MENINGKATKAN KESADARAN METAKOGNITIF DAN HASIL BELAJAR SISWA MELALUI PENERAPAN PEMBELAJARAN PROBLEM SOLVING - Sukaisih, Roniati; Muhali, Muhali (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2014)
The purpose of this study is to increase metacognitive awareness and student learning achievement through the implementation of Problem Solving learning. Learning achievement in this study include the cognitive, affective, and psychomotor aspects on temperature and heat learning material. This study used Classroom action research conducted in 3 cycles consisting of planning, implementation, observation, evaluation, and reflection. Students’ metacognitive awareness data obtained through metacognitive awareness questionnaire and students’ activity in worksheet used to control Students’ metacognitive awareness. Student learning achievement was taken with multiple-choice test techniques for cognitive learning achievement, practicum activities and presenting practicum results for affective and psychomotor learning achievement tailored to affective and psychomotor indicators. The conclusion of this research is through the implementation of Problem Solving learning can increase metacognitive awareness and student learning achievement.